2007
DOI: 10.1177/004947550703700219
|View full text |Cite
|
Sign up to set email alerts
|

Critical care management of gynaecological patients in Enugu, Nigeria

Abstract: A retrospective study of the management of gynaecological patients admitted to the general intensive care unit (ICU) of the University of Nigeria Teaching Hospital (UNTH), Enugu, Nigeria, over a 6-year span was carried out. Out of a total of 816 patients admitted to the ICU during the study period, 21 (2.6%) were gynaecological patients with the following diagnoses: generalized sepsis, postoperative respiratory distress, hypovolaemic shock, preoperative anaemia and mennorhagia, and major surgery with potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
0
1
Order By: Relevance
“…The values (2.51 -4.16%) obtained in this study were similar to the ash content (2.49 -4.12%) of yam flour fortified with soy-pomace reported by Gbenga et al [22]. The ash content of a food material could be used as an index for estimating the mineral constituents of such a food product [23].…”
Section: Proximate Composition Of Soy -Poundo Yam Composite Blendssupporting
confidence: 89%
See 2 more Smart Citations
“…The values (2.51 -4.16%) obtained in this study were similar to the ash content (2.49 -4.12%) of yam flour fortified with soy-pomace reported by Gbenga et al [22]. The ash content of a food material could be used as an index for estimating the mineral constituents of such a food product [23].…”
Section: Proximate Composition Of Soy -Poundo Yam Composite Blendssupporting
confidence: 89%
“…Manganese helps the body in the formation of connective tissues, bones, blood clotting factors and sex hormones. It also plays significant roles in fat and carbohydrate metabolism as well as in calcium absorption and in the regulation of blood sugar level in the body [23].…”
Section: Mineral Composition Of Soy-poundo Yam Composite Blendsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean value for IgG anti-B titer was 69.33±4.65 as compared to 44.39±4.92 for IgG anti-A. These findings are not consistent with that of (Olawumi and Olatunji, 2001;Worlledge et al, 1974;Okafor and Enebe, 1985) who all found anti-A hemolysins occurring more frequently than anti-B hemolysins.…”
Section: Discussioncontrasting
confidence: 70%